Long-term prospective clinical follow-up after BRCA1/2 presymptomatic testing: BRCA2 risks higher than in adjusted retrospective studies. Issue 9 (22nd July 2014) - Evans, D Gareth; Harkness, Elaine; Lalloo, Fiona; Howell, Anthony
Abstract : Background: The risks of breast cancer associated with BRCA1 and BRCA2 mutations vary considerably across studies but few have assessed prospective risks, which are likely to provide more reliable risk estimates for women undergoing presymptomatic testing. Methods: Prospective breast cancer risks were assessed in 254 unaffected women with BRCA1 mutations and 238 with BRCA2 mutations. Rates of breast cancer were calculated allowing for lead time bias and censored at time of risk reducing mastectomy. Degree of family history was assessed using the Manchester score and genotyping was undertaken using 18 single-nucleotide polymorphisms (SNPs) linked to breast cancer. Results: Nineteen breast cancers occurred in women undergoing presymptomatic testing for BRCA1 and 23 for BRCA2 . Breast cancer incidence for BRCA2 was marginally higher than BRCA1 at 20.05 per 1000 in BRCA2 compared with 16.20 per 1000 in BRCA1 . Penetrance estimates to 70 years of age adjusted for a 6-month lead time and oophorectomy using Kaplan–Meier analysis were 55.1% (95% CI 36.5% to 75.6%) for BRCA1 and 71.5% (95% CI 53.2% to 87.6%). Breast cancer cases were associated with stronger family histories and higher SNP aggregate scores in BRCA2 . Conclusions: Prospective breast cancer risks in women in the UK are high especially for BRCA2 families ascertained on the basis of high risk. Women undergoing presymptomatic testing for BRCA2 should be quoted a wide range of possible breast cancer risks and should be steered within that range based on degree of family history, non-genetic risk factors and possibly SNP testing.